2017
DOI: 10.1186/s12891-017-1521-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and symmetrical patellofemoral pain patterns as revealed by high-resolution 3D body mapping: a cross-sectional study

Abstract: BackgroundDetailed pain mapping of extent and distribution in individuals with patellofemoral pain (PFP) within and around a complex structure such as the knee has yet to be explored.MethodsPerceptions of on-going pain from adolescents and young adults (N = 35) with long-standing (>10 months) PFP were collected on high-resolution 3D digital body-schema of the knees. Location, area of pain, pain intensity, laterality, worse side of knee pain, symptom duration, and symmetry in bilateral knee pain were recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 35 publications
6
50
1
Order By: Relevance
“…Patellofemoral pain (PFP) is a common and frequently persistent condition that presents as pain behind or around the patella [1,2]. It is typically considered to have a mechanical aetiology, aggravated when the knee is loaded in a flexed position [3], with ensuing functional limitations in daily physical tasks and sporting activities [4].…”
Section: Introductionmentioning
confidence: 99%
“…Patellofemoral pain (PFP) is a common and frequently persistent condition that presents as pain behind or around the patella [1,2]. It is typically considered to have a mechanical aetiology, aggravated when the knee is loaded in a flexed position [3], with ensuing functional limitations in daily physical tasks and sporting activities [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the amount of detail, as shown in Figure 2, and easier quantification of pain areas and patterns are more readably achieved with digital solutions. Additional benefits include the ability to contrast one or more pain drawings at different time points, to determine common features within or between patient populations [4,5], and to map other qualities of pain or discomforts [11], such as burning or aching sensations. indeed, other methods of digitizing pain drawings exist, such as scanning paper drawings and modifying pre-existing paint and drawing tools [4].…”
Section: Moving Forward With Digital Technologiesmentioning
confidence: 99%
“…in the recent two decades, data stemming from simple methods of musculoskeletal pain drawing have helped to reveal the significance of single versus multi-site pain reports. Presently, digital pain mapping studies show that there may be hidden patterns of pain expression within these marked pain sites [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have investigated pain drawings recorded on digital platforms and shown reliability commensurate with that of paper drawings [11 12] A study using high-resolution and contoured (3D) images of the knee found a high proportion of patients with patellofemoral pain (PFP) reported knee pain in mirrored locations and that the pain drawings were exceptionally symmetrical. [12] Interestingly, when the knee pain drawings were compared to duration of symptoms, those with a longer duration of symptoms appeared to draw patterns more of an 'O' shape. Given that longer duration of PFP symptoms has been shown to be a prognostic indicator of a poor outcome, [13] capturing pain areas digitally will allow quantification and real time insight into the patient's condition, which may optimise patient management.…”
Section: Introductionmentioning
confidence: 99%